A Narrative Pharmacological Review of Buprenorphine: A Unique Opioid for the Treatment of Chronic Pain - Gudin, Jeffrey (Pain Ther, 2020)
Buprenorphine is a Schedule III opioid analgesic with unique pharmacodynamic and pharmacokinetic properties that may be preferable to those of Schedule II full μ-opioid receptor agonists. The structure of buprenorphine allows for multimechanistic interactions with opioid receptors μ, δ, κ, and opioid receptor-like 1. Buprenorphine is considered a partial agonist with very high binding affinity for the μ-opioid receptor, an antagonist with high binding affinity for the δ- and κ-opioid receptors, and an agonist with low binding affinity for the opioid receptor-like 1 receptor. Partial agonism at the μ-opioid receptor does not provide partial analgesia, but rather analgesia equivalent to that of full μ-opioid receptor agonists. In addition, unlike full μ-opioid receptor agonists, buprenorphine may have a unique role in mediating analgesic signaling at spinal opioid receptors while having less of an effect on brain receptors, potentially limiting classic opioid-related adverse events such as euphoria, addiction, or respiratory depression. The pharmacokinetic properties of buprenorphine are also advantageous in a clinical setting, where metabolic and excretory pathways allow for use in patients requiring concomitant medications, the elderly, and those with renal or hepatic impairment. The unique pharmacodynamic and pharmacokinetic properties of buprenorphine translate to an effective analgesic with a potentially favorable safety profile compared with that of full μ-opioid receptor agonists for the treatment of chronic pain.